THE SEXUAL HARASSMENT FACED BY WOMEN IN KATE ELIZABETH RUSSELL’S “MY DARK VANESSA”: A STUDY OF THE MAIN CHARACTER - Puspa Pradini, Safitri Dyah; Widisanti, Ni Made; Kristyowati, Dyah (Journal Albion : Journal of English Literature, Language, and Culture, 2024)
ABSTRACTThis research was designed to show the sexual harassment experienced by the main female character in the novel My Dark Vanessa by Kate Elizabeth Russell. Her name is Vanessa, a 15-year-old minor student who was sexually abused by her English teacher, Strane. The descriptive analysis method describes the problems that occur with the main female character. The research technique employed is library research. The study encompasses both intrinsic elements, such as plot, characters, setting, irony and conflict, as well as extrinsic elements such as child sexual abuse, gender concepts from a cultural perspective, the concept of love, Post-Traumatic Stress Disorder (PTSD), and power relations, as per Michel Foucault's theories. The research results prove that sexual harassment occurs because of the patriarchal culture and the power relations that dominate. Sexual harassment can have several causes, including psychological conditions, different concepts of love, and the setting. It often leads to feelings of Post-Traumatic Stress Disorder (PTSD) in the victim, which requires psychotherapy for treatment. Additionally, the victim may need to work on self-acceptance as a part of her healing process from the trauma she has experienced.Keywords: Sexual harassment; sexual assault; woman; patriarchy